THE EFFECTIVENESS OF PROJECT BASED LEARNING (PjBL) WORKSHEET TO IMPROVE SCIENCE PROCESS SKILL FOR SEVEN GRADERS OF JUNIOR HIGH SCHOOL IN THE TOPIC OF ENVIRONMENTAL POLLUTION - Citradevi, Cindy Paramita; Widiyatmoko, Arif; Khusniati, Miranita (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The science learning process is not only learn how to remember the materials, but also capable in science process skill and apply knowledge in scientific work. Through science process skill in learning science, the study is no longer focused on the end result, but also on the process. Project activity is one of learning activities which is appropriate to develop science process skill, through a project students can be actively involved in learning and able to understand the concepts. Project activites can be fasilitated by teaching material in the form of worksheets because its more practical in its use. The purpose of this study was to determine the effectiveness of the use of project based learning worksheet on pollution in enhancing science process skills and understanding of the concept of students. This study was an experimental with the type of quasi-experimental research design. The experiment was conducted in Junior High School 7 Magelang with research subjects students of grade VII. The results showed the average percentage of science process skills students experimental class was 91% with good criteria once the fourth meeting, with the average percentage the first meeting was 39% with a sufficient criteria. Class control has an average percentage of science process skills of students is 45% with not good criteria on the fourth meeting, with the average percentage the first meeting is 36%. Understanding the concept of experimental class students have increase in average the value of N-gain of 0.46. As well as the experimental class has an average value of understanding the concept of a higher grade than the control based on the calculation of the t test with tcountâ‰¥ttable (4.80â‰¥1.67). Thus, project based learning worksheet on pollution effectively used to improve the understanding of the concept and science process skills of students.